Family, failure and fatigue in the field - Henni Alava; Megan Robertson (African Journal of Gender and Religion (AJGR))
Many feminist scholars have experienced receiving critique for what are claimed to be overly narrative, emotional, or insufficiently scholarly pieces of writing. This piece speaks to this experience. The text was originally read as a presentation in a webinar on 'Patchwork Ethnography'. In resisting the coerciveness of dominant academic rhetorical codes, the paper calls for researchers to be more transparent about the devastating effects of patriarchy and neoliberal academia on their personal and professional lives. The choices we make about what and how we research; what and where we publish; and how we write; can and should contribute to countering those effects, and envisioning and enacting a world where being an academic doesn't hurt.